IMPLEMENTASI WEBSITE UBPESS SEBAGAI PLATFORM INTERAKSI ANONIM MAHASISWA UNIVERSITAS BUANA PERJUANGAN KARAWANG - Fergy Izvan Riskiyanto; Shofa Shofiah Hilabi; Fitria Nurapriani; Baenil Huda (PT. Hasba Edukasi Mandiri, 2026)
The development of information technology has encouraged the creation of more interactive digital communication media in academic environments; however, the lack of controlled anonymous platforms makes it difficult for students to express their opinions freely and safely. This study aims to design and implement the UBPess website as an anonymous interaction platform for students of UBP Karawang using the ADDIE method. The system provides features such as anonymous message posting (menfess), user interaction, authentication using the institutional email domain ubpkarawang.ac.id, and email verification to ensure user validity. Additionally, the system includes a context-based automatic language filtering feature to screen inappropriate content before publication and real-time notifications. The results indicate that the UBPess system has been successfully implemented and is capable of meeting the need for an interactive, controlled, and secure anonymous communication platform within the campus environment, with the language filtering feature serving as an added value in maintaining content quality.